Energy Management Method for solar race car design and application - Ustun, O.; Yilmaz, M.; Gokce, C.; Karakaya, U.; Tuncay, R. N. (IEEE, 2009)
The Energy Management Method for designing a solar-cell supplied electrical vehicle is described and its implementation on Istanbul Technical University (ITU) race cars is discussed. The effectiveness of the method has been tested and proved during the 2006, 2007 and 2008 races organized by the Scientific and Technical Council of Turkey. The “Energy Management Model (EMS)”, which computes the energy consumption of the virtual vehicle on the virtual race track. For this purpose, electrical and mechanical components of the vehicle are modeled and the energy values are calculated while vehicle computer model is running on three dimensional model of the test track. When the maximum performance scenario, which means maximum possible speed for available energy, is obtained, then brushless dc machine and its driver are designed accordingly. A data acquisition system is formed to measure vehicle's electrical and electromechanical quantities. This information is send to the main computer through a wireless communication system. The main computer runs the energy management program and controls whether the race is progressing suitable with the best race scenario. If any discrepancy between simulation and experiment is detected a new optimum scenario is defined and implemented. With this flexible method, maximum performance is achieved by neither flatting the battery in the middle of the race nor remaining partially charged at the finish line.